Development of Bilingual Snap Book to Increase The Local Medicinal Plants Knowledge of Primary School Students - Dhuta Sukmarani; Azza Azkiya; Sukma Wijayanto; Sheik Mohamed (JIPI (Jurnal IPA & Pembelajaran IPA), 2025)
Despite Indonesia’s rich medicinal-plant biodiversity, primary education has not adequately integrated this knowledge into age-appropriate and bilingual learning media, leading to limited understanding among elementary school students. This research aims to develop and test the effectiveness of a bilingual snap book as a learning medium to increase the knowledge of primary school students about local medicinal plants. The study was conducted using the research and development (R&D) method with the ADDIE (analyze, design, develop, implement, and evaluate) model. The product developed is an interactive full-color bilingual snap book equipped with magnetic stick-and-release features to help students actively learn about local medicinal plants in Indonesian and English. The media was validated by five experts in health, education, biology, language, and media fields, resulting in a content validity ratio (CVR) and content validity index (CVI) score of 1.00, indicating that the media is valid and feasible for use. The implementation phase was carried out with 20 fifth-grade students at MIM Teladan Magelang City. The results of the pretest and posttest analysis showed an increase in the average score from 61.11 to 73.44. The wilcoxon signed ranks test produced a significance value of 0.000 (p < 0.05), indicating a significant improvement in students’ knowledge after using the media. These findings show that the bilingual snap book is valid, practical, and effective in enhancing students’ understanding of local medicinal plants and supporting the development of environmental care attitudes. In addition, its bilingual format contributes to improving both science and language literacy among primary school students